The Influence of Think Talk Write Learning Strategies on Critical Thinking Skills and Student’s Learning Outcomes of Islamic Religious Education Subjects - Wandira, Wahyuni; Sukardi, Ismail; Oviyanti, Fitri; Sari, Ana Kurnia (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The purpose of this research is to determine the influence of the Think Talk Write strategy in learning Islamic Religious Education material about belief in the Last Day on critical thinking and student learning outcomes. The design of this research is a pretest and posttest control group design. The population of this study was class V of SD Negeri 1 Kuala Sungai Pasir, where the sample consisted of 2 classes using a random class technique (Simple Random Sampling). Class Va as an experimental class uses the Think Talk Write learning strategy, while class Vb as a control class uses conventional learning strategies. Data collection techniques use observation sheets and written tests, consisting of a pretest and posttest totaling 35 questions. Data were analysed using inferential statistical analysis. Based on the results of critical thinking research, for the t test it was found that t-count = 26.286 while t-table = 2.052. The learning results, for the t test, show that t-count = 31.745 while t-table = 2.052, which means that t-count > t-table so H0 is rejected and Ha is accepted. The conclusion from the results of this research is that there is an influence of the Think Talk Write learning strategy on critical thinking and student learning outcomes at SD Negeri 1 Kuala Sungai Pasir.